Molybdenum reduction to molybdenum blue in Serratia sp. strain DRY5 is catalyzed by a novel molybdenum-reducing enzyme - Shukor M.Y.; Halmi M.I.E.; Rahman M.F.A.; Shamaan N.A.; Syed M.A. (Hindawi Publishing Corporation, 2024)
Indexed by Scopus